The Role of fact-checking sites during the Israel-Palestine conflict - Reza, Raiyan; Sunvy, Ahmed Shafkat (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2023)
As a result of the information explosion, a great amount of data has been created, including stuff that is deceptive, ethically problematic, tolerant, and hateful. The rapid and extensive circulation of false news, on the other hand, appears to show that many people either do not comprehend the concept of